2001
DOI: 10.1074/jbc.m008802200
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Regulates Vascular Smooth Muscle Cell Growth and Heat Shock Proteins via the JAK-STAT Pathway

Abstract: The growth-stimulating effects of thrombin are mediated primarily via activation of a G protein-coupled receptor, PAR-1. Because PAR-1 has no intrinsic tyrosine kinase activity, yet requires tyrosine phosphorylation events to induce mitogenesis, we investigated the role of the Janus tyrosine kinases (JAKs) in thrombin-mediated signaling. JAK2 was activated rapidly in rat vascular smooth muscle cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 67 publications
7
85
2
Order By: Relevance
“…As previously demonstrated by others (52,53) and by us (31), besides Jak2-mediated tyrosine phosphorylation, full STAT1␣ activation in response to IFN-␥ appears to require ERK1/2-dependent serine phosphorylation. In line with these findings, separate studies have shown that both ERK1/2 and STAT1␣ serine phosphorylation are impaired by Jak2 inactivation (54,55). We found that MSU ϩ IFN-␥-inducible activation of the ERK1/2 pathway was necessary for their synergistic effect on iNOS and NO regulation.…”
Section: Discussionsupporting
confidence: 75%
“…As previously demonstrated by others (52,53) and by us (31), besides Jak2-mediated tyrosine phosphorylation, full STAT1␣ activation in response to IFN-␥ appears to require ERK1/2-dependent serine phosphorylation. In line with these findings, separate studies have shown that both ERK1/2 and STAT1␣ serine phosphorylation are impaired by Jak2 inactivation (54,55). We found that MSU ϩ IFN-␥-inducible activation of the ERK1/2 pathway was necessary for their synergistic effect on iNOS and NO regulation.…”
Section: Discussionsupporting
confidence: 75%
“…Of interest, both ERK1/2 and STAT1␣ serine phosphorylation were found to be impaired by Jak2 inactivation (58,59). Therefore, it is conceivable that the noticed abrogation of HZ ϩ IFN-␥-inducible NO synthesis by selective blockage of Jak2 is due to the central role played by this kinase in iNOS transcriptional regulation, both by directly phosphorylating STAT1␣ on its tyrosine residue and by increasing ERK-dependent STAT1␣ serine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The increased response to a PAR-1 agonist and the up-regulation of PAR-1 expression in intestinal smooth muscle were absent in STAT6 Ϫ/Ϫ mice, indicating that PAR-1-induced hypercontractility in N. brasiliensis infection is STAT6 dependent. Thrombin activates JAK2, which is linked to STAT2 and STAT4 signaling in vascular smooth muscle cells (25); thus, it is conceivable that PAR-1 also acts through JAK pathways linked to STAT6.…”
Section: Discussionmentioning
confidence: 99%